Medium/Heavy Duty Truck Engines, Fuel & Computerized Management Systems, 6th Edition - Sean Bennett (Cengage Learning, 2020)
Ideal for students, entry-level technicians, and experienced professionals, the fully updated Sixth Edition of MEDIUM/HEAVY DUTY TRUCK ENGINES, FUEL & COMPUTERIZED MANAGEMENT SYSTEMS is the most comprehensive guide to highway diesel engines and their management systems available today. The new edition features expanded coverage of natural gas (NG) fuel systems, after-treatment diagnostics, and drive systems that rely on electric traction motors (including hybrid, fuel cell, and all-electric). Three new chapters address electric powertrain technology, and a new, dedicated chapter on the Connected Truck addresses telematics, ELDs, and cybersecurity. This user-friendly, full-color resource covers the full range of commercial vehicle powertrains, from light- to heavy-duty, and includes transit bus drive systems. Set apart from any other book on the market by its emphasis on the modern multiplexed chassis, this practical, wide-ranging guide helps students prepare for career success in the dynamic field of diesel engine and commercial vehicle service and repair.